Barriers and facilitators of psychosocial service provision for patients with cancer across six hospitals in Ethiopia: a qualitative study - Belay, Winini; Ware, Finina Abebe; Kaba, Mirgissa; Addissie, Adamu; Kantelhardt, Eva Johanna; Wondimagegnehu, Abigiya (Frontiers in Psychiatry, 2025)
BackgroundWhile psychosocial services are known to improve treatment adherence and quality of life for cancer patients by mitigating anxiety and depression, evidence from Ethiopia is limited. A recent trial introduced integrated psychosocial interventions, including counseling, group discussions, educational materials, and home visits, into routine care. The present study explores barriers and facilitators affecting psychosocial service provision in selected Ethiopian hospitals.MethodA qualitative study was conducted at six hospitals across four regions of Ethiopia, where psychosocial support had been introduced and provided to patients with cancer. Data were collected through in-depth interviews (IDIs) and focus group discussions (FGDs) with patients diagnosed with breast, cervical, or colorectal cancer; as well as key informant interviews (KIIs) with healthcare professionals, including oncologists, gynecologists, surgeons, nurses, and health extension workers. All interviews were transcribed, translated and reviewed for completeness. To enhance data familiarity, transcripts and audio recordings were reviewed multiple times. NVivo software was used for data management and organization. Data was coded inductively while predefined themes are introduced deductively, followed by thematic analysis to identify key patterns and insights.ResultBarriers to psychosocial support (PSS) in cancer care include limited awareness of its importance, as treatment is often considered to be purely medical. Although home visits are common in maternal health, in cancer care, they face resistance due to unfamiliarity. Disclosure challenges also persist, with providers avoiding sensitive conversations, leaving patients under-informed. Hospital leadership tends to prioritize physical care over PSS. However, survivor stories enhance patient reassurance and openness; travel reimbursements and refreshments facilitate patient participation and communication, and routine supervision of PSS activities supports provider effectiveness in PSS provision.ConclusionIntegrating PSS into routine cancer care requires a shift in the mindset of patients, providers, and leadership, recognizing PSS as an essential component of comprehensive cancer care. Raising awareness about home visits and strengthening provider skills through targeted training on disclosure can improve patient engagement and quality of care.